How Necessary is the Vasculature in the Life of Neural Stem and Progenitor Cells? Evidence from Evolution, Development and the Adult Nervous System - Koutsakis, Christos; Kazanis, Ilias (Frontiers in Cellular Neuroscience, 2016)
Augmenting evidence suggests that such is the functional dependence of neural stem cells (NSCs) on the vasculature that they normally reside in “perivascular niches”. Two examples are the “neurovascular ” and the “oligovascular ” niches of the adult brain, specialized microenvironments where NSCs or oligodendrocyte progenitor cells survive and remain mitotically active in close proximity to blood vessels. In addition, the often observed co-ordination of angiogenesis and neurogenesis led to these processes being described as “coupled”. Here, we adopt an evo-devo approach to argue that some stages in the life of a NSC, such as specification and commitment, are independent of the vasculature, while stages such as proliferation and migration are largely dependent on blood vessels. We also explore available evidence on the possible involvement of the vasculature in other phenomena such as the diversification of NSCs during evolution and we provide original data on the senescence of NSCs in the subependymal zone stem cell niche. Finally, we will comment on the other side of the story; on how much is the vasculature dependent on NSCs and their progeny.